The position of new media in the announced and executive policies of the Ministry of Education of the Islamic Republic of Iran: A study of cyberspace - seyyed mohammad ali shakib; Naser Bahonar; sesyed mohsen banihasemi; bahram alishiri (Religion & Communication)
The growth and development of new communication technologies and their effects in the form of new media on the educational process of students has become an important concern for families and cultural-educational policy makers in the country. And highlights the need to address this issue in formal policies, especially in the field of education. The present study uses a qualitative research method (document research and in-depth interviews with directors of education) in order to enumerate the announced and executive policies of education and also compare them in the face of cyberspace to examine and describe the current state of interaction of the formal education institution with this The media has paid. From the collection and selection of approved and related documents of announced policies, the main axes include: hardware equipment, software production and knowledge production, information technology education, culture in the field of new media, research and studies in the field of information technology, education cooperation with other institutions and policy approach to New media was extracted. Executive policies in three general areas of policy, approach-attitude, operational-executive were extracted from in-depth interviews with directors of education.Finally, declarative and executive policies, in order to extract the depth of the difference between what is approved in the written documents, And what has been done on the ground, Based on the main policy axes, functional axes, normative principles were compared and analyzed. Based on this comparison, it can be concluded that there are deep attitudinal and conceptual gaps between the policies announced by the country's formal education system and its executive policies in the face of new media.